ENHANCING STUDENTS' DIGITAL LITERACY: OPTIMIZING GOOGLE CLASSROOM IN TECHNOLOGY-BASED LEARNING - Hallaby, Syarifah Fadiya; Arifitama, Budi (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2025)
Digital literacy is an essential competency for university students navigating academic and professional environments in the digital era. Despite the widespread adoption of Google Classroom as a learning management system, its effective utilization remains constrained by gaps in digital proficiency and a lack of structured training. This academic service initiative seeks to enhance students' digital literacy by providing targeted instruction on optimizing Google Classroom for academic purposes. Through interactive workshops, participants engage in hands-on learning to master key functionalities of Google Classroom, including task organization, academic discourse facilitation, and resource management. Post-training assessments indicate a significant improvement in students' ability to navigate digital learning environments, demonstrating enhanced self-directed learning capabilities and more effective academic collaboration. This initiative contributes to the broader goal of fostering digital readiness in higher education, equipping students with the skills necessary to engage meaningfully in technology-driven learning environments. Future programs are recommended to expand the scope of training, integrate advanced pedagogical strategies, and ensure equitable access to digital learning resources for all students. Keywords: digital literacy, technology-based learning, Google Classroom.